functionalization of hydrogel for metals detection - คำแพงศรี ศาษติญา; แก้วทอง ชาติไทย (Progress in Applied Science and Technology, 2018)
Hydrogels are cross-linked hydrophilic polymers, and they have been functionalized with many substrates to make sensors. The advantages of hydrogel sensors over conventional sensors are that they have tree-dimensional structure, biocompatibility, large sensor loading capacity, easy to modifier and very low optical background. In this review, I overview three types of hydrogel sensors for selectively removing metal ions (i) Crown ethers-functionalized hydrogels, (ii) Protein or DNA-functionalized hydrogels, and (iii) Polymer-functionalized hydrogels.